A robust impact angle constraint guidance law with seeker's field-of-view limit. (March 2015) - He, Shaoming; Lin, Defu
In this paper, a new robust guidance law is designed to satisfy both impact angle constraint and the seeker's field-of-view limit for missiles with strapdown seekers. Since the impact angle guidance law needs a highly curved trajectory and most strapdown seekers have a very narrow field-of-view, maintaining the seeker's lock-on is the key issue for these missiles. To address this problem, a switching logic is adopted, which adds an additional term in the original guidance law when the look angle exceeds the pre-designed boundary value to maintain the seeker's lock-on. An impact angle guidance law is designed based on terminal sliding mode control theory and the finite time convergence characteristic of the line-of-sight angle, as well as its derivative is proved through the Lyapunov method. Numerical simulations are performed to validate the effectiveness of the proposed guidance law. Some intuitive tunings of the design parameters are also offered in the simulation results to achieve large impact angles.